Private Supplementary Tutoring Centers’ Performance in Iran: Students, Principals and Officers’ Opinions - Arani, Abbas Madandar (Education Sciences, 2018)
For over three decades, private supplementary tutoring has become a common educational phenomenon in Iran. One of the most common forms of private tutoring in Iran was centers that operated with the permission from the Ministry of Education. The aim of this study was to evaluate the performance of these centers through students, principals and officers’ opinions. The sample population of this study was made up of 249 students, 53 principals and 23 officers of education bureau who were selected through a multi-stage cluster sampling method from five different provinces of Iran. The findings revealed that students indicated that private centers have a relatively poor and inappropriate level of facilities. With respect to the objective and goal of these institutes, most of the students found that tutors have a good level of professional knowledge, using appropriate teaching methods and constantly evaluated learners abilities through different exams. In contrast, there was a serious disagreement between principals and officers’ opinion about centers’ performance with regards to their educational roles and common offenses.